The Similarity Between Chinese Five-Pattern and Eysenck’s Personality Traits: Evidence From Theory and Resting-State fMRI - Zhao, WenTao; Song, LiPing; Du, Jian; Li, XiaoZhen; Wang, Hao; Cheng, Long; Li, Jing; Zhang, Liang; Li, XinRong; Yang, QiuLi; Xu, Yong (Frontiers in Human Neuroscience, 2020)
Chinese five-pattern and Eysenck’s personality traits are two types of personality theories based on different cultural backgrounds. The former is an indigenous theory, and the latter is a cross-cultural theory. In order to verify the relationship between two different personality traits from theory and neuropsychology, the current study recruited 170 healthy adults to calculate their five-Pattern Personality Inventory (FPPI) and Eysenck Personality Questionnaire-Revised (EPQ) scales and to scan their brains using functional magnetic resonance imaging (fMRI). Then, we performed stepwise-regression analysis and mediation-effect analysis to explore the association between brain regional homogeneity (ReHo) and two types of personality traits. The results showed that the ReHo of the right superior temporal gyrus (STG) positively correlated with TaiYang traits for FPPI and that there was a significant linear relationship with extraversion and neuroticism for EPQ. Besides, the ReHo of the right medial prefrontal cortex (mPFC) positively correlated with TaiYin for FPPI, and it also showed a significant linear relationship with neuroticism for EPQ. Furthermore, we found that extroversion and neuroticism partially mediated the relationship between five-pattern personality traits and the regional brain function, based on the mediation-effect analysis. Our findings suggest that Chinese five-pattern personality traits have a close relationship with Eysenck’s personality traits and that both may be engaged in similar neurobiological mechanisms in common brain regions to some extent. Hence, these findings first reveal a relationship between Chinese traditional personality traits and Western Eysenck’s personality traits in terms of both theoretical and neurobiological contexts.